Approximate Mathematical Model of an Absorption Heat Pump with Steam Heating for Integration in the Steam Turbine Thermal Scheme - SHUBENKO, O.; BABAK, M.; SENETSKYI, O. (Science and Innovation, 2024)
Introduction. The results of theoretical and experimental studies presented in the literature have shown that CHPPs have a signifi cant potential for energy savings when operating on a heat load by improving thermal schemes and operating characteristics. Solving the problem of improving the power plant turbine generator thermal scheme by implementing an absorption heat pump (AHP) improves the effi ciency of the use of fuel and energy resources in the heat and electricity production. Problem Statement. An analysis of literary sources has shown that in recent years, more and more attention has been paid to utilizing secondary sources of powerful power units operating in cogeneration mode with a signifi cant supply of thermal energy to consumers. The presence of waste non-utilizable heat leads to a decrease in the effi ciency of the use of initial fuel resources. This negatively aff ects the cost of heat and electricity and has a negative impact on the environment. Purpose. The purpose of this research is to develop a fairly simple approximate mathematical model of AHP with steam heating (conversion coeffi cient μ = 1.71), which is based on the real thermal transformers characteristics and is applicable in solving problems of its integration and to study the level of changes in the material fl ows of a powerful steam turbine with an integrated AHP with steam heating during a heating season. Material and Methods. A simple approximation mathematical model based on the real characteristics of thermotransformer has been proposed to determine the AHP characteristics. It can be used to solve the problems of its integration into the thermal schemes of CHPP cogeneration units. The considered algorithm serves as a basis for creating software modules for determining the characteristics of AHP. Results. An approximate mathematical model of AHP with steam heating for solving the problems of integrating a heat pump in the cogeneration plant thermal schemes on the basis of the interpolation dependences of pump characteristics and conservation equations has been proposed and designed. Conclusions. The proposed approximation mathematical model of AHP makes it possible to evaluate the performance of a cogeneration plant for heating season when AHP of the corresponding thermal power is integrated into the thermal scheme of steam turbine under a signifi cant heat supply load.